Self-Efficacy Family Caregiver dalam Merawat Pasien Demensia: Studi Deskriptif di RSUP Dr. Sardjito, Indonesia - Anggraini Lizdiana Wulandari; Heny Suseani Pangastuti; Christantie Effendy (Jurnal Keperawatan Klinis dan Komunitas (Clinical and Community Nursing Journal), 2020)
Background: Dementia symptoms gradually hinder patients’ ability to perform daily activities, necessitating support from various parties particularly family caregivers. Self-efficacy is believed to have a positive influence on family caregivers, contributing to improved mental health, adaptive coping, and reduced psychological distress when dealing with the challenges associated with dementia patient care. Despite these potential benefits, research on family caregiver self-efficacy in caring for dementia patients in Indonesia remains limited, making this study necessary. Objective: To explore the self-efficacy of family caregivers in treating dementia patients. Methods: The study is quantitative descriptive approach employed a cross-sectional design involving 53 family caregivers of dementia patients from the Memory Clinic of RSUP Dr. Sardjito, Indonesia, selected through purposive sampling. The research instrument used was the Caregiver Self-efficacy Scale (CaSES). Univariate analysis was employed using mean and standard deviation scores for numeric ratio data. Results: The study identified four domains assessing family caregivers’ self-efficacy, with an average value of 3,09 ± 0,84. The domains included self-maintenance 3,18 ± 0,81, emotional connectivity 3,05 ± 0,87, instrumental caregiving 3,15 ± 0,82, and resilience 2,99 ±0,85. Conclusion: The results indicated that family caregivers exhibit relatively high levels of self-efficacy in treating dementia patients. Notably, family caregivers demonstrated the highest self-efficacy in the self-maintenance domain and the lowest in the resilience domain.ABSTRAKLatar belakang: Gejala demensia secara bertahap menghambat kemampuan pasien untuk melakukan aktivitas sehari-hari sehingga memerlukan dukungan dari berbagai pihak terutama pengasuh keluarga. Self-efficacy diyakini memiliki pengaruh positif bagi family caregiver dalam hal peningkatan kesehatan mental, penyesuaian diri yang adaptif, dan pengurangan tekanan psikologis saat menghadapi tantangan yang terkait dengan perawatan pasien demensia. Meskipun memiliki potensi manfaat tersebut, penelitian mengenai self-efficacy family caregiver dalam merawat pasien demensia di Indonesia masih terbatas, sehingga penelitian ini menjadi penting. Tujuan: Untuk mengeksplorasi self-efficacy family caregiver dalam merawat pasien demensia. Metode: Penelitian ini deskriptif kuantitatif menggunakan desain cross sectional dengan melibatkan 53 pengasuh keluarga pasien demensia dari Klinik Memori RSUP Dr. Sardjito, Indonesia, yang dipilih melalui purposive sampling. Instrumen penelitian yang digunakan adalah Caregiver Self-efficacy Scale (CaSES). Analisis univariat digunakan dengan menggunakan nilai mean dan standar deviasi untuk data rasio numerik. Hasil: Penelitian ini mengidentifikasi empat domain self-efficacy dengan nilai rata-rata sebesar 3,09 ± 0,84. Domain-domain tersebut meliputi self-maintenance 3,18 ± 0,81, emotional connectivity 3,05 (SD ± 0,87, instrumental caregiving 3,15 ± 0,82, dan resilience 2,99 ± 0,85. Kesimpulan: Hasil penelitian menunjukkan bahwa para family caregiver memiliki tingkat self-efficacy yang relatif tinggi dalam merawat pasien demensia. Secara khusus, para pengasuh keluarga menunjukkan self-efficacy tertinggi dalam domain self-maintenance dengan terendah domain resilience.